Comparison of spatial interpolators for variability analysis of soil chemical properties in Cuamba (Mozambique) - Costa, Ana Cristina (2018)
Costa, A. C., & Bofana, J. D. R. (2017). Comparison of spatial interpolators for variability analysis of soil chemical properties in Cuamba (Mozambique). African Journal of Agricultural Research, 12(25), 2153-2162. https://doi.org/10.5897/AJAR2016.12415